The extent to which internet school students are used in school libraries within karak Education schools - Abu- Smhadaneh, Emad Ahmad Zedan (Journal of Educational and Psychological Sciences, 2021)
The study aims to explore the current reality of internet service in school libraries affiliated with the education of Karak by identifying the advantages and disadvantages of the service and identifying the most important problems facing the use of the Internet in school libraries. The study also aimed to knew the views and perspectives of each of the managers, secretaries and employees of school libraries on the impact of the Internet service in their libraries. The study gains its importance by addressing the issue of the Internet and its basic services in school libraries and its importance and benefits in the scientific research process. The study population consists of students of the education schools in Karak Governorate from the preparatory and secondary school levels. The study sample is represented in the Kasbah of Karak schools for males and females for the preparatory and secondary stages. The researcher used the descriptive, analytical approach and the case study approach. The researcher collected data through books and periodicals that dealt with the Internet topic and the interview with the librarian and the questionnaire. The study came out with a set of findings and recommendations for students and librarians, which will help develop the use of the Internet in school libraries.
Keywords: Use of the library; librarians; Education of the karak Kasbah